Desarrollo de una iniciativa web 2.0 para fomentar la difusión cultural del cantón Machala, año 2016. - Nieves Quishpe, Mónica Alexandra (2017)
Communication is being enriched by new technologies of access to knowledge, and a culture born of digital communication is born, for which the internet is the greatest exponent at a global level and since the internet became a mass media in the 90s has revolutionized The way of informing us, of communicating and of our life in general. It has advanced rapidly to respond to the multiple needs of users, resulting in web 2.0 that refers to a trend where the content of the network is developed by a community of users who share, transform content and socialize, That is why it is said that this is a social web. In the development of this research we have contact with a group of students of the Technical University of Machala of the career of Social Communication, in order to know the level of interactivity and knowledge that the students have on these platforms. To do this, you used these drawer questions. Do you know what Web 2.0 platforms are? Do you apply them to develop your daily activities? To which most of them demonstrated to have basic knowledge of these technologies and little use of them, rather than to fulfill academic activities. This interaction allowed us to conceive the idea of a digital proposal in relation to the cultural history of Canton Machala, resulting in the development of a Web 2.0 initiative that allows the dissemination of its roots. Web 2.0 is a platform in which students and teachers can share what they learn collaboratively with facilitators and experts. One of the applications of the Web 2.0 is the wiki that are used in group tasks based on projects that allow to correct the content, and even for the final presentation of the work